Sarasvatīkaṇṭhābharaṇasya Bhojarājasya Sāhityaprakāśo nāma Śr̥ṅgāraprakāśaḥ - Bhojarāja (Indirāgāndhīrāṣtrīyakalākendram ; Kālidāsasaṃsthānam ; Vitarakaḥ Motīlāla Banārasīdāsa Pabliśarsa, 2007)
Treatise on Sanskrit poetics and aesthetics; critical edition.